Implementasi Hidroponik Sebagai Bentuk Pertanian Modern Guna Meningkatkan Ketahanan Pangan di Desa Musir Lor - Hendra Maulana; Andhika Yudha Fachriza; Mohamad Fikri Azam; Widyana Dini Maylinda; Indra Rasendriya Pratama; Nirwana Septania Galih Perwira Moekti (Lembaga Pengembangan Kinerja Dosen, 2023)
The agricultural sector is one of the main and very important sectors for Indonesian economy because many Indonesian people work as farmers spread throughout Indonesia. the number of requests for rice raw materials is not fulfilled due to various kinds of obstacles experienced by farmers. One of the problems in Musir Lor Village as a village with a majority of the population working as farmers is the lack of land that can be used for farming and the weakness of farmers' ability to be able to develop their agricultural products. For this reason, technology is needed to be able to help solve the problems faced by farmers in Musir Lor Village. KKNT 65 students from UPN Veteran Jawa Timur help them to overcome the existing problems by holding discussion about Hydroponic planting media also practice to make simple Hydroponics for the people of Musir Lor Village The implementation of socialization activities carried out at the Musir Lor Village Hall on May 11th 2023 which was attended by around 32 people. The socialization included an explanation of the meaning of hydroponics, presentation of material about the advantages of hydroponics, explanation of the tools and materials needed, then there was a training session for installing hydroponic frames and carrying out seeds who then transferred the planting from rockwool to the hydroponic framework, the series of hydroponic socialization events was closed with a question and answer session related to what had been conveyed. Furthermore, there are also controlling activities that will last for few weeks to ensure that the plants can grow properly.